Cash transfers and management advice for agriculture: Evidence from Senegal - Ambler, Kate; de Brauw, Alan; Godlonton, Susan (International Food Policy Research Institute, 2017)
This study analyzes impacts of large, one-time cash transfers and farm management plans among farmers in Senegal. Farmers were randomized into groups receiving advisory visits, the visits and an individualized farm plan, or the visits, the plan, and a cash transfer. After one year, crop production and livestock ownership were higher in the transfer group relative to the group that only received visits. Livestock gains persisted after two years. Results suggest that the plans increased crop production in year one, but there is no other evidence that the plans were effective when not accompanied by a transfer.